Deliberative Public Consultation via Deliberative Polling: Criteria and Methods - Fishkin, James S. (The Hastings Center report, 2021)
This article poses the problem of public consultation on contested policies involving new technologies and competing values or value-laden goals. It argues that Deliberative Polling, an approach developed by the author, can be usefully employed to engage representative samples to deliberate in depth in controlled experiments so as to yield a picture of the public's considered judgments. It also argues from recent experience that such consultations can be cost effectively conducted online with stratified random samples. It draws on examples from various issue domains including climate and energy as well as prototype deliberations conducted on gene editing in the wild. It sets out criteria that Deliberative Polling, as well as other designs, should satisfy if policy recommendations based on the data generated by these public consultations are to be credible.